Substituting The Synthetic For The Authentic: The Contribution of Rudolf Steiner’s Biodynamic Innovations in Advancing Yos Suprapto’s Traditional Knowledge of Local Agriculture - M. Dwi Marianto; Rob Goodfellow; Hanggar Budi Prasetya; Mita Purbasari Wahidiyat (Institut Seni Indonesia Denpasar, 2023)
In 1970, Indonesian President Suharto’s New Order Government formally adopted an international system of agricultural production known as ‘The Green Revolution.’ This required Indonesian farmers to adopt so-called modern farming practices as part of the first five-year national development program, which incorporated an emphasis on ‘Swasembada Pangan,’ or food production self-sufficiency. Chemical-based fertilizers, fungicides, herbicides and pesticides have been in continuous and widespread use in conventional farming in Indonesia ever since. Concurrently, international peer-reviewed scientific research has reported the detrimental effects of their widespread use on complex ecosystems, in particular, on pollinating insect populations such as bees. This situation greatly concerns many people, including Yos Suprapto, an Indonesian artist who articulates his social engagement through non-conventional creative practice. Since 2009, Suprapto has pioneered rice planting using the biodynamic agriculture (BDA) system developed in 1924 by the Austrian educator and innovator Rudolf Steiner. Yos Suprapto argues that, as with art, farming also requires innovation and novelty as well as an intimate understanding of human systems. This includes, an appreciation of the shortcomings associated with the modern world, namely reliance on complex manufacturing processes, often located abroad, and increasingly vulnerable and disrupted international supply chain networks. Farming, then, is Yos Suprapto’s ‘canvas’ and the colors he ‘paints’ are his crops and his ability to not just see the world as it is but as it should be. This study uses productive hermeneutic and aesthetic engagement theories to better understand why Yos Suprapto has insisted on implementing organic farming techniques and how he has also taken advantage of local oral traditions, local materials, and indigenous locally-produced rice varieties to increase harvest yields without the use of synthetic fertilizers and, in doing so, support and advance not only traditional knowledge and time-honoured cultural practices, but also local human food security.